2008
DOI: 10.1038/ijir.2008.33
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled study of postoperative nightly sildenafil citrate for the prevention of erectile dysfunction after bilateral nerve-sparing radical prostatectomy

Abstract: Four weeks after bilateral nerve-sparing radical retropubic prostatectomy, men with normal erectile function before surgery were randomized to double-blind sildenafil (50 or 100 mg) or placebo nightly for 36 weeks, followed by an 8-week drug-free period before assessment of erectile function. Enrollment was prematurely ceased and only 76 men completed because, assuming a placebo response rate similar to the published literature (for example, 34% in meta-analysis), the 25% response at blinded interim review sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
228
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(236 citation statements)
references
References 31 publications
2
228
0
6
Order By: Relevance
“…43 Penile rehabilitation after nerve-sparing radical prostatectomy: Clinical evidence Despite all the evidence in favor of chronic treatment with PDE5-I, only a few trials have assessed the role of penile rehabilitation in men who underwent RP. [46][47][48][49][50][51][52] Montorsi et al 46 demonstrated that, by using intracorporeal injections of alprostadil early after bilateral NSRP (BNSRP), the rate of recovery of spontaneous erections was significantly higher than the rate with observation alone. Those data also recently were confirmed by Mulhall et al,47 who demonstrated that the prophylactic use of intracorporeal injections of alprostadil in patients who did not respond to oral sildenafil resulted in higher rates of spontaneous functional erections and erectogenic drug response 18 months after NSRP.…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Penile rehabilitation after nerve-sparing radical prostatectomy: Clinical evidence Despite all the evidence in favor of chronic treatment with PDE5-I, only a few trials have assessed the role of penile rehabilitation in men who underwent RP. [46][47][48][49][50][51][52] Montorsi et al 46 demonstrated that, by using intracorporeal injections of alprostadil early after bilateral NSRP (BNSRP), the rate of recovery of spontaneous erections was significantly higher than the rate with observation alone. Those data also recently were confirmed by Mulhall et al,47 who demonstrated that the prophylactic use of intracorporeal injections of alprostadil in patients who did not respond to oral sildenafil resulted in higher rates of spontaneous functional erections and erectogenic drug response 18 months after NSRP.…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 99%
“…The rationale for the use of these drugs as prophylaxis is based mainly on oxygenation of the corpora cavernosa, thus maintaining a vital cavernosal structure. Padma-Nathan et al 49 reported on the prospective administration of sildenafil at doses of 50 mg and 100 mg versus placebo, daily and at bedtime, in patients who underwent BNSRP and were potent preoperatively. Four weeks after surgery, the patients were randomized to receive either sildenafil or placebo for 36 weeks.…”
Section: Pharmacologic Prophylaxis Of Postoperative Erectile Dysfunctmentioning
confidence: 99%
“…A number of RCTs have reported on the effects of daily PDE5i use on postoperative erectile function with discordant results. 5,6,14,15 In addition, there is strong evidence demonstrating that PDE5i affect and improve LUTS. 16 Moreover, an association between LUTS and erectile dysfunction has been clearly established, and recently reviewed by Mouli and McVary.…”
Section: Discussionmentioning
confidence: 99%
“…The International Index of Erectile Function questionnaire was then administered, revealing that 27% of the treatment group reported return of spontaneous erection sufficient for intercourse versus 4% in the placebo group 1 year after surgery. 41 A further study was performed to test nocturnal penile tumescence using a 54-patient subset of this group. A total of 10 out of 35 treatments (4/17 of 50 mg sildenafil recipients and 6/18 of 100 mg sildenafil recipients) and 1 out of 19 placebo recipients were responders, defined by at least 55% penile-based rigidity for at least 10 min.…”
Section: Penile Rehabilitationmentioning
confidence: 99%